1999
DOI: 10.1046/j.1365-2222.1999.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactivity between milk proteins from different animal species

Abstract: Homologies in amino acidic composition could justify the cross-reactivity observed between proteins from different animal species. On the other hand, the phylogenetic difference could be responsible for the failed recognition of camel's proteins by circulating IgEs and monoclonal antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
1
11

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 24 publications
7
97
1
11
Order By: Relevance
“…This non-recognition suggests the absence of β-Lg to the dromedary milk [11][12][13][14] . These results are in accordance with those of [17] . Indeed this researcher showed that the proteins of dromedary milk seem to be the only proteins which had not been recognized by serum antibodies of IgE type of children allergic to proteins in cow's milk.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This non-recognition suggests the absence of β-Lg to the dromedary milk [11][12][13][14] . These results are in accordance with those of [17] . Indeed this researcher showed that the proteins of dromedary milk seem to be the only proteins which had not been recognized by serum antibodies of IgE type of children allergic to proteins in cow's milk.…”
Section: Resultssupporting
confidence: 93%
“…In addition to that and according to Restani et al. [17,18] the cross reactions were observed between proteins of milk and meats, such as caseins and albumin, of different species like the cow, goat, ewe and mare and it was explained by the probable resemblance in the sequence of their proteins.…”
Section: Resultsmentioning
confidence: 81%
“…Because of high cross-reactivity (up to 80%) and nutritional inadequacy, the use of most animal milk is precluded (28)(29)(30). Rice based hydrolysates, available in certain countries, may offer an alternative approach in the treatment of CMPA.…”
Section: Fig 2 Decision Tree For Diagnosis and Treatment Of Formulamentioning
confidence: 99%
“…Sheep's milk mixed with camel's milk at a 50%: 50% ratio raised the protein content of cheese. On the other hands, camel milk is considered a useful component of the diet for individuals that show allergic reactions to the protein fraction of cow, ewe or goat milk, as camel milk does not contain ß-lactoglobulin and the content of alpha-casein is much lower than in milk of other herbivores mentioned [27,28]. Significant differences were reported in the fat content among the five types of cheeses (Table 4).…”
mentioning
confidence: 99%